Measuring Usability Of Poscast As An Alternative Form In Education : A Case Study In Programming Subject - Hairol Hisham, Hamdan (2008)
This research is to measure the usability of Podcast in educational field especially for student of Universiti Utara Malaysia respectively and their acceptance upon the technology. The dimension being measure are perceived of usefulness, learnability, flexibility, attitude and behavioral intention within the Podcast usage. The data being collected using a questionnaire form and the sample are focusing on 150 Bachelors Degree students in College of Arts and Sciences which taking programming subject (TIA1023). The result has stated that almost half of the sample satisfied and happy by using Podcast as an additional and alternative material form in their learning process.